Dual-Use “New Space”: US Experience - D. V. Stefanovich; A. S. Ermakov (Международная аналитика, 2024)
The article explores the growing involvement of private space companies in military activities, with a primary focus on the United States. It delves into the specific contributions of private entities to national defense missions, particularly in the militarization of outer space. The authors analyze the strategic interests of government agencies in integrating non-state actors to enhance space capabilities, such as communication, Earth observation, situational awareness, and in-orbit servicing. The paper also assesses the potential implications of these trends for international security, highlighting the complexities that arise from the blurred lines between civil and military space operations. It points to the creation of the U.S. Commercial Augmentation Space Reserve (CASR), an initiative aimed at enhancing defense through commercial space partnerships, and discusses the operational and strategic challenges of managing vast satellite constellations. Additionally, the article reflects on the security risks posed by the militarization of commercial space infrastructure, examining the potential consequences for geopolitical stability and the future of space conflict management. Finally, it suggests that further research and regulatory measures are necessary to mitigate the military threats linked to the New Space